1996
DOI: 10.1097/00000372-199608000-00007
|View full text |Cite
|
Sign up to set email alerts
|

An Immunohistochemical Study of p53 Protein Expression in Classical Kaposi's Sarcoma

Abstract: The present study was performed to determine the frequency of p53 protein immunoreactivity in classical Kaposi's sarcoma (KS) as a whole and in relation to the histological subtypes which are considered to correspond to the developmental stages of the tumor. The accumulation of p53 protein was studied immunohistochemically using monoclonal antibody BP53-12 on formalin-fixed paraffin-embedded sections of 36 KS lesions, of which 14 were classified histologically as early type and 22 as spindle-cell or mixed type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In this context, it is interesting to note that two latent proteins that are tightly coexpressed with K cyclin, LANA and v-FLIP, respectively compromise activation of p53 (63) and promote tumorigenesis by inhibiting lymphocyte apoptosis (64). In addition, KSHV-associated disorders do not display recurrent p53 mutations (65)(66)(67), and LANA was found to colocalize with p53 in KS samples (66). Together with our findings, this therefore suggests an intriguing interplay between latent viral proteins in promoting survival and proliferation of KSHV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it is interesting to note that two latent proteins that are tightly coexpressed with K cyclin, LANA and v-FLIP, respectively compromise activation of p53 (63) and promote tumorigenesis by inhibiting lymphocyte apoptosis (64). In addition, KSHV-associated disorders do not display recurrent p53 mutations (65)(66)(67), and LANA was found to colocalize with p53 in KS samples (66). Together with our findings, this therefore suggests an intriguing interplay between latent viral proteins in promoting survival and proliferation of KSHV-infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse, KS-like lesions as KS can sporadically regress in humans (51,154). In contrast, it has been reported that KSC obtained from late-stage KS show in some cases a transformed phenotype, as indicated by the acquisition of monoclonality (141), microsatellite instability (20), altered expression of proto-oncogenes (22,25,88,102,161), and the capability of promoting tumor development in mice (84,117). These findings suggest that KS develops as a reactive process which, in time, may evolve into a true sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the viral homologues of the FLICE inhibitory proteins and cyclins D may provide KSC and endothelial cells with growth and/or antiapoptotic signals (46,115,172,(175)(176)(177). The long-lasting expression of these HHV-8 latency genes together with the deregulated expression of cellular oncogenes and/or oncosuppressor genes, including int-2, c-myc, bcl-2, and p53 (22,25,88,102,161), are likely to participate in KS progression toward a real tumor. These findings suggest that the role of HHV-8 in KS pathogenesis may be more important after KS initiation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the expression of p53 varies in different stages of KS progression. The expression of p53 was hardly detectable in the early stage of KS, but the percentage of p53-positive cells increased in the more advanced stage (2,18,34,45,55,62,71). Apparently, the absence of p53 results in a disadvantage for cells in controlling the aberrant proliferation that is induced by KSHV viral proteins, such as K-cyclin.…”
Section: Discussionmentioning
confidence: 98%